Exploring the ethical, legal, and social implications of cybernetic avatars - Shineha, Ryuma (Frontiers in Robotics and AI, 2026)
A cybernetic avatar (CA) is a concept that encompasses not only avatars representing virtual bodies in cyberspace but also information and communication technology (ICT) and robotic technologies that enhance the physical, cognitive, and perceptual capabilities of humans. CAs can enable multiple people to remotely operate numerous avatars and robots together to perform complex tasks on a large scale and create the necessary infrastructure for their operation and other related activities. However, due to the novelty of this concept, the ethical, legal, and social implications (ELSI) of CAs have not been discussed sufficiently. Therefore, the objective of this paper is to provide an overview of ELSI in the context of a CA, taking into account the implications from fields similar to that of CAs, such as robotic avatars, virtual avatars, metaverses, virtual reality, extended reality, social robots, human–robot interaction, telepresence, telexistence, embodied technology, and exoskeletons. In our review of ELSI in related fields, we found common themes: safety and security, data privacy, identity theft and identity loss, manipulation, intellectual property management, user addiction and overdependence, cyber abuse, risk management in a specific domain (e.g., medical applications), regulatory gaps, balance between free expression and harmful content, accountability, transparency, distributive justice, prevention of inequalities, dual use, and conceptual changes of familiarity. These issues should not be ignored when considering the social implementation of CAs.